Análisis de mercado para determinar índices de penetración de banda ancha en las parroquias rurales: Santiago, Taquil y Gualel del cantón Loja y propuesta técnica-económica de factibilidad para implementar infraestructura de telecomunicaciones usando tecnología GPON-FTTC. - Salcedo Carrión, José Pablo S (2020)
This work aimed to improve the broadband penetration rates in rural areas such as Santiago, Taquil, and Gualel. Proposing an FTTC access network with GPON technology for the least favored rural areas with internet service to meet the demand of users who require the service to improve the quality of life of the people who live in the sector. Furthermore, to achieve this, a market analysis was carried out to obtain data on the quality of internet service, existing telecommunications infrastructure, and companies that provide internet service in these areas. The network design was carried out based on the CNT EP regulations and ITU-T recommendations in order to demonstrate the design's validity through economic feasibility analysis, considering the network design's implementation costs. Keywords : FTTC, GPON, Loja, parroquias rurales, CNT EP.